Recycled material-containing container and method for manufacturing recycled material-containing container

By adding organic peroxide and titanium dioxide to the recycled materials, the fluidity and strength unevenness of the recycled materials and new materials are solved, and a recycled material container with excellent color consistency and mechanical properties is achieved, which is suitable for modular stacking.

JP2025018725APending Publication Date: 2025-02-06GIFU PLAST IND CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023122701
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-27
Publication Date
2025-02-06

AI Technical Summary

Technical Problem

In the prior art, when using recycled materials and new materials to make injection molding, there are problems of uneven fluidity and strength, especially in thin-walled containers. At the same time, the uneven color of the recycled materials leads to inconsistent color tones of the container, making it difficult to use compatible with traditional containers.

Method used

By adding appropriate amounts of organic peroxide and titanium dioxide to the mixed materials, adjusting the flowability and color of the recycled materials, ensuring compatibility with new materials, and adopting mold design and injection molding processes with specific structures to ensure uniform flow and strength of the materials.

Benefits of technology

The fluidity and strength of the recycled material container are consistent with that of the new material container, and are close in color, suitable for modular stacking, and have excellent mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025018725000003
    Figure 2025018725000003
  • Figure 2025018725000001
    Figure 2025018725000001
  • Figure 2025018725000002
    Figure 2025018725000002
Patent Text Reader

Abstract

To provide a recycled material-containing container that has excellent strength and a gray color with brightness similar to that of a gray molded product made from virgin materials.SOLUTION: A method for manufacturing a recycled material-containing container by injection-molding a gray mixed material including virgin material comprising polypropylene resin and recycled material containing polypropylene resin includes a mixing step of mixing the virgin material with the recycled material. In the mixing step, the recycled material to be mixed is modified by adding an organic peroxide and adding titanium oxide to be from 2 mass% to 10 mass% inclusive. This ensures that the melt flow rate of the mixed material is 40 g / 10 min or more and that the Izod impact value is 8.0 kJ / m2 or more.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a container containing recycled materials, which is made by mixing virgin synthetic resin material with recycled materials, and a method for manufacturing the same. [Background technology]

[0002] There are containers for sorting and storing parts to be used in a factory or for sorting and storing products to be sold in a store. These containers may be molded by injection molding, in which molten resin is injected into a mold and then cooled and hardened.

[0003] Patent Document 1 describes an invention relating to an integrally molded container molding method in which a container is injection molded using a fixed mold and a movable mold. Patent Document 1 describes that when molding a thin-walled container in response to a request for a lighter, thinner container, a plurality of resin gates are provided on the side wall and bottom wall to prevent bias in the flow of resin in the cavity. This is to ensure the fluidity of the resin and the strength of the molded product. In other words, in order to ensure the fluidity of the resin in the cavity narrowed by the request for a thinner container, it is necessary to increase the melt flow rate of the resin, but if the melt flow rate is increased, there is a problem that it is difficult to ensure the strength of the molded product. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Patent No. 5557485 Summary of the Invention [Problem to be solved by the invention]

[0005] However, due to the growing concern about the environment in recent years, there is a demand for using recycled materials made of discarded resin materials as materials for molding containers. However, recycled materials generally have a small melt flow rate. Therefore, when virgin materials are mixed with recycled materials and injection molded, there may be a difference in melt flow rate between the virgin material and the recycled material, making it difficult to obtain uniform fluidity. If uniform fluidity is not obtained, the compatibility between the two is not good. This may affect the strength of the molded product.

[0006] In addition, the melt flow rate of the entire mixed material containing recycled materials is also reduced, which reduces the fluidity of the mixed material in the mold. This is also thought to reduce the strength of the molded product. In particular, when molding a container with a thinner wall to reduce weight, the influence of the fluidity of the mixed material is significant. In this way, the problem of ensuring the strength of the molded product while increasing the melt flow rate is also common to containers containing recycled materials.

[0007] In addition, recycled materials tend to be mixed with various resin materials, which makes them black in color. If the color cannot be the same as that of the gray containers made from regular virgin materials, containers of various colors will be mixed together, making them difficult to use. [Means for solving the problem]

[0008] In order to solve the above problems, the manufacturing method of the recycled material-containing container of the present invention is a manufacturing method of a recycled material-containing container by injection molding a gray mixed material obtained by mixing a virgin material made of polypropylene resin with a recycled material containing polypropylene resin, and includes a mixing step of mixing the virgin material with the recycled material, and in the mixing step, an organic peroxide is added and the recycled material that has been modified by adding titanium oxide so that the content is 2% by mass or more and 10% by mass or less is mixed, and the melt flow rate is 40 g / 10 min or more and an Izod impact value is 8.0 kJ / m 2 The above-mentioned mixed material is prepared.

[0009] In the above configuration, it is preferable that the recycled material modified by adding an organic peroxide so that the organic peroxide content is 0.2% by mass or more and 1.5% by mass or less is mixed in the mixing step. In the above-mentioned configuration, in the mixing step, the recycled material modified by adding titanium oxide in an amount of 2 mass% to 10 mass% is mixed, so that the specific gravity of the mixed material is 0.91 g / cm 3 More than 1.02g / cm 3 It is preferable to set the following:

[0010] In the above-mentioned configuration, the recycled material is L * It is preferable that the value of the modified recycled material is 31 or more and 35 or less, and that in the mixing step, titanium oxide is added so that the modified recycled material has a content of 2% by mass or more and 6% by mass or less.

[0011] In order to solve the above problems, the recycled material-containing container of the present invention is a gray recycled material-containing container made by mixing a virgin material made of polypropylene resin and a modified recycled material containing polypropylene resin, and contains titanium oxide in an amount of 0.2% by mass or more and 5.0% by mass or less and has a specific gravity of 0.91 g / cm 3 More than 1.02g / cm 3 is less than or equal to L * The value is 36 or more and less than 65, the flexural modulus is 1100MPa or more, and the Izod impact value is 8.0kJ / m 2 That's all.

[0012] In the above construction, the melt flow rate is preferably 40 g / 10 min or more. Effect of the Invention

[0013] According to the present invention, a container containing recycled materials can be obtained which is excellent in strength and has a gray color with a brightness similar to that of a molded product made from virgin material. [Brief description of the drawings]

[0014] [Figure 1]FIG. 1 is a perspective view of a container according to the present embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] Hereinafter, a recycled material containing container according to one embodiment of the present invention will be described. The recycled material containing container 1 (hereinafter referred to as the container 1) of this embodiment is used, for example, to sort and store parts used in an assembly plant according to specifications.

[0016] <About Container 1> As shown in FIG. 1, the container 1 is a rectangular parallelepiped box of approximately 25 cm x 50 cm x 25 cm, consisting of a bottom wall 11 and four side walls 12. The upper part of the side walls 12 forms an opening that opens upward. The bottom surface of the bottom wall 11 has six protrusions 14 reinforced by ribs 13. All six protrusions 14 have the same shape and size. Between the protrusions 14, grooves 15 are formed that extend perpendicularly. The grooves 15 have the same width.

[0017] The container 1 of this embodiment is a container 1 that can be used in a modularized form. A plurality of containers 1 can be stacked, and containers 1 of different sizes can also be stacked. In the case of containers 1 of different sizes, for example, the container 1 is a cubic box, and four convex portions 14 of the same shape and size are formed on the bottom surface of the bottom wall 11. It is preferable that the aspect ratio of the bottom wall 11 of the container 1 is up to about 6.0. In order to use the container 1 in a modularized form, a group of square-shaped ribs 13 is formed on the convex portions 14. In order to use the container 1 in a modularized form, the color tone needs to be uniform.

[0018] When multiple containers 1 are stacked, the upper end of the side wall 12 of the lower container 1 fits into the groove 15 extending along the outer periphery of the bottom wall 11 of the upper container 1. In addition, since the grooves 15 extend perpendicularly, multiple containers 1 can be stacked with a horizontal offset.

[0019] The container 1 is a so-called thin container in which the side wall 12 has a relatively thin wall thickness. The wall thickness of the side wall 12 is preferably about 1.7 to 2.9 mm, and more preferably about 1.9 to 2.5 mm. In order to reinforce the side wall 12, a plurality of vertical flanges 16 extending in the up-down direction and horizontal flanges 17 extending in the horizontal direction are formed on the side wall 12. The vertical flanges 16 and the horizontal flanges 17 are formed to be thicker than the side wall 12. This improves the strength of the container 1.

[0020] The container 1 is manufactured by injection molding a mixed material obtained by mixing virgin material made of polypropylene resin with a recycled material that contains polypropylene resin and has been modified (hereinafter referred to as modified recycled material).

[0021] In addition, recycled materials may generally contain polyethylene or polyvinyl chloride in addition to polypropylene. If such resins are mixed in, the mixed material may not flow uniformly when the container 1 is molded. Furthermore, since the bottom surface of the container 1 has alternating convex portions 14 and concave grooves 15, the flow of the resin injected from the gate is unlikely to be constant. Therefore, in order to stabilize the flow of the mixed material at the concave groove 15 and make it easier to flow to the rib 13, the width of the concave groove 15 is set to be more than twice the length of the rib 13. Also, the thickness of the base of the rib 13 is thicker than the thickness of the bottom wall 11. This is because the recycled material is mixed in and is more likely to deform than the virgin material alone. Also, the difference in shrinkage makes the material more likely to deform.

[0022] Recycled materials are used after being processed by crushing discarded synthetic resin products. Recycled materials include polypropylene resin as the main component, mixed with other materials such as polyethylene resin and polyvinyl chloride resin, and polypropylene resin that is unevenly mixed with block polypropylene resin, random polypropylene resin, and homopolypropylene resin. Therefore, compared to containers made only of virgin materials, containers 1 mixed with recycled materials have a different color tone and are inferior in mechanical properties such as fluidity, bending strength, and impact resistance.

[0023] Generally, recycled materials are a mixture of synthetic resin materials of different tones, so they have low brightness and are close to black. On the other hand, conventional gray containers, which are injection molded from virgin materials to sort and store parts according to their specifications, have a brightness of L. * The value is about 45 to 60. From the viewpoint of being easy to use together with conventional containers injection molded only from virgin materials and being useful as a substitute for conventional containers, the container 1 of this embodiment is molded using a mixed material in which a virgin material is mixed with a recycled material (modified recycled material) modified by adding titanium oxide. By adding titanium oxide to the recycled material, the brightness of the modified recycled material can be made closer to that of the virgin material, and the brightness of the container 1 can be made closer to that of a container molded from conventional virgin materials.

[0024] The amount of titanium oxide added to the recycled material is preferably 2% by mass or more and 10% by mass or less, more preferably 2% by mass or more and 6% by mass or less, and even more preferably 2% by mass or more and 4% by mass or less, relative to 100 parts by mass of the recycled material. When the amount of titanium oxide added is within this range, the brightness of the mixed material into which the modified recycled material is mixed approaches the brightness of the virgin material. In other words, it does not become too whitish or too blackish compared to the virgin material. L, which represents the brightness of the modified recycled material, * The value is preferably 36 or more and less than 70, more preferably 36 or more and less than 65, and even more preferably 45 or more and less than 60.

[0025] In addition, the lightness of the mixed material, that is, the lightness of the container 1 obtained by injection molding the mixed material in which the virgin material is mixed with the modified recycled material, is expressed by L * The value is preferably 36 or more and less than 70, more preferably 36 or more and less than 65, and even more preferably 45 or more and less than 60. * If the value falls within this range, the container will have the same brightness as a conventional container made only of virgin material, making it easy to use.

[0026] By modifying the recycled material by adding titanium oxide, the mixed material preferably contains titanium oxide in an amount of 0.2 mass % or more and 5.0 mass % or less. By adding titanium oxide to the recycled material to modify it, the specific gravity of the mixed material increases. The specific gravity of virgin polypropylene material is 0.9 g / cm 3 whereas the specific gravity of the mixed material, i.e., container 1, is 0.91 g / cm 3 More than 1.02g / cm 3 It is preferable that:

[0027] When the container 1 shown in FIG. 1 is injection molded, for example, in an injection mold, molten resin material (mixed material) is injected into a cavity from a resin gate formed at a position corresponding to the center of the bottom wall 11. Therefore, if the fluidity of the mixed material is low, the molten resin does not sufficiently spread throughout the cavity, causing a deterioration in the quality of the molded product. This is particularly noticeable when the container 1 is large or has a thin wall thickness. In the container 1 of this embodiment, the vertical flange 16 and the horizontal flange 17 are formed to be thicker than the side wall 12 for reinforcement. Therefore, good fluidity is required because a large amount of resin needs to be poured.

[0028] From the viewpoint of ensuring the strength of the molded product by ensuring that the mixed material obtained by mixing the modified recycled material with the virgin material is sufficiently distributed in the cavity, the container 1 of this embodiment is molded using a mixed material obtained by mixing a virgin material with a recycled material modified by adding an organic peroxide (organic peroxide modified recycled material). This makes the melt flow rate (MFR), which indicates the fluidity of the modified recycled material, close to the MFR of the virgin material, and makes the MFR of the mixed material equal to or higher than a predetermined value. By making the MFR of the modified recycled material close to the MFR of the virgin material, the compatibility between the modified recycled material and the virgin material is improved, and the deterioration of the physical properties of the molded container 1 can be suppressed.

[0029] The MFR of the modified recycled material is preferably 20g / 10min or more, more preferably 40g / 10min or more. When the MFR of the modified recycled material is in this range, it has good compatibility with virgin materials. It is possible to suppress uneven mixing when the modified recycled material is mixed with the virgin material.

[0030] The MFR of the mixed material is preferably 40 g / 10 min or more. In other words, the MFR of the resin constituting the molded container 1 is preferably 40 g / 10 min or more.

[0031] On the other hand, when organic peroxide is added to the recycled material to modify it, the mechanical properties such as bending strength and impact strength of the molded container 1 may be deteriorated. Therefore, the amount of organic peroxide added needs to be adjusted taking into account the balance between the MFR value and the mechanical properties of the molded product.

[0032] The amount of organic peroxide added to the recycled material is preferably 0.2% by mass to 1.5% by mass, more preferably 0.2% by mass to 0.8% by mass, and even more preferably 0.2% by mass to 0.6% by mass, based on 100 parts by mass of the recycled material. When the amount of organic peroxide added is within this range, the MFR of the container 1 is 40 or more, the flexural modulus is 1100 MPa or more, and the Izod impact value is 8 kJ / m 2If the organic peroxide content is 1.5% by mass or less, the decrease in impact strength of the container 1 can be suppressed.

[0033] The amount of organic peroxide added to the recycled material can be reduced if the following two formulas are satisfied: (Formula 1)A>B×0.25 (Formula 2)(A×a / 100)+(B×b / 100)>B×0.8 Here, A is the MFR of the recycled material, a is the amount of recycled material mixed, B is the MFR of the virgin material, and b is the amount of virgin material mixed.

[0034] <About the manufacturing method of Container 1> Next, a manufacturing method of the container 1 will be described together with its function. The manufacturing method of the container 1 includes a modification step of modifying the recycled material, a mixing step of mixing the modified recycled material with virgin material, and a molding step of injecting the mixed material into a mold and injection molding it.

[0035] In the modification step, titanium oxide and organic peroxide are added to the recycled material to obtain a modified recycled material (a titanium oxide modified recycled material and an organic peroxide modified recycled material). Titanium oxide and organic peroxide may be added separately or simultaneously. When added separately, titanium oxide may be used as a resin material (master patch) in which the recycled material and titanium oxide are kneaded.

[0036] As described above, the amount of titanium oxide added is preferably 2% by mass to 10% by mass, more preferably 2% by mass to 6% by mass, and even more preferably 2% by mass to 4% by mass, relative to 100 parts by mass of the recycled material. Also, as described above, the amount of organic peroxide added is preferably 0.2% by mass to 1.5% by mass, more preferably 0.2% by mass to 0.8% by mass, and even more preferably 0.2% by mass to 0.6% by mass, relative to 100 parts by mass of the recycled material.

[0037] In the mixing step, the modified recycled material is added to the virgin material and kneaded. The temperature during kneading is preferably about 200 to 250° C. The modified recycled material has a high MFR due to the addition of the organic peroxide, and the difference in MFR with the virgin material is small, so the compatibility with the virgin material is good and uneven mixing is suppressed.

[0038] In the molding process, for example, a molding die consisting of a fixed die and a movable die in which a resin gate is formed is set at a position corresponding to the center of the bottom wall 11 of the container 1. After the die is clamped, the mixed material in a molten state is injected into the formed cavity through the resin gate.

[0039] The mold used in the molding process of this embodiment has an L / T of 250 or more, where L is the flow length from the resin gate to the end of the container 1, which is the farthest position, and T is the thickness of the cavity. In other words, the wall thicknesses of the bottom wall 11 and the side wall 12 are relatively thin compared to the size of the container 1. In this regard, since the MFR of the mixed material is adjusted to 40 g / 10 min or more, the mixed material spreads from the resin gate at a position corresponding to the central part of the bottom wall 11 toward the region corresponding to the bottom wall 11 and the region corresponding to the side wall 12 in the cavity. With uneven mixing suppressed, the mixed material spreads to the rib 13 of the convex portion 14 and the region corresponding to the vertical flange 16 and the horizontal flange 17 of the side wall 12. In this way, the mixed material is evenly distributed to the end of the cavity. Thereafter, the mold is cooled and demolded to obtain the container 1.

[0040] According to the container 1 and the manufacturing method thereof of this embodiment, the following effects can be obtained. (1) Container 1 is made by injection molding a grey mixed material made of virgin polypropylene resin and modified recycled material containing polypropylene resin. The mixed material constituting container 1 contains 0.2% to 5.0% by mass of titanium oxide, giving it a specific gravity of 0.91 g / cm. 3 More than 1.02g / cm 3 is less than or equal to L *The value is 36 or more and less than 65. Also, the Izod impact value is 8.0 kJ / m 2 As a result, even though the container 1 contains recycled materials, it has the same color (brightness) and strength as a container made only from virgin materials.

[0041] (2) The container 1 has a melt flow rate of 40 g / 10 min or more. Since the container 1 is injection molded from a mixed material with such a melt flow rate, the resin spreads well in the mold, resulting in a container 1 with excellent moldability.

[0042] (3) In the manufacturing method of the container 1, in the mixing step of mixing the virgin material with the recycled material, an organic peroxide is added and a modified recycled material with titanium oxide added so that the titanium oxide content is 4% by mass or more and 15% by mass or less is mixed. As a result, the melt flow rate of the mixed material is 40 g / 10 min or more, and the Izod impact value of the container 1 is 8.0 kJ / m 2 As a result, a gray container 1 having excellent strength can be manufactured.

[0043] (4) In the mixing process, the modified recycled material is mixed with organic peroxide so that the content is 0.2% by mass or more and 1.5% by mass or less. This results in a mixed material with excellent fluidity and an MFR of 40g / 10min or more.

[0044] (5) In the mixing step, the modified recycled material is mixed with titanium oxide so that the content is 2% by mass or more and 10% by mass or less, so that the specific gravity of the mixed material is 0.91 g / cm 3 More than 1.02g / cm 3 Therefore, the luminance of container 1 is expressed as follows: * It can be any grey value between 35 and 65.

[0045] (6) L, which represents the brightness of recycled materials *When the value is 31 or more and 35 or less, in the mixing step, titanium oxide is added so that the content is 2 mass% or more and 6 mass% or less, and the modified regenerated material is mixed. This results in the L * The value is set to 45 or more and 65 or less. Therefore, it is possible to make the container gray in the same color as a container made only of conventional virgin materials, and it is easy to use even if both materials are mixed.

[0046] The above embodiment can be modified as follows: The above embodiment and the following modified examples can be applied in combination with each other to the extent that there is no technical contradiction. The shape of the container 1 is not limited to that shown in Fig. 1. The vertical flanges 16 and the horizontal flanges 17 may be omitted. Also, the protrusions 14 and the recessed grooves 15 may be omitted.

[0047] The size and wall thickness of the container 1 are not limited to those described above. The molding die does not necessarily have to have a resin gate formed in the center of the bottom wall 11. Also, a molding die having multiple resin gates may be used, or a molding die having multiple resin gates only on the bottom wall 11 may be used.

[0048] The technical ideas that can be understood from the above-described embodiments will be described below. (A) A method for manufacturing a container containing recycled materials by injection molding a gray mixed material obtained by mixing a virgin material made of polypropylene resin with a recycled material containing polypropylene resin, the method including a mixing step of mixing the virgin material with the recycled material, in which an organic peroxide is added in an amount of 0.2% by mass to 1.5% by mass and titanium oxide is added in an amount of 2% by mass to 6% by mass to the recycled material, and the recycled material is modified by mixing the modified material, thereby increasing the melt flow rate of the mixed material to 40 g / 10 min or more and the lightness L * The value must be between 45 and 65, and the flexural modulus of the container containing recycled materials must be 1100 MPa or more and the Izod impact value must be 8.0 kJ / m 2 A method for manufacturing a container containing recycled materials, characterized in that the above is achieved.

[0049] (b) The recycled material has a brightness of L * In the mixing step, the recycled material is modified by adding titanium oxide in an amount of 2% by mass to 6% by mass, and the L * The method for producing the container containing recycled materials comprises preparing the mixed material having a value of 36 or more and less than 65.

[0050] (c) A method for manufacturing a recycled material-containing container, in which a grey mixed material is obtained by mixing a virgin material made of polypropylene resin with a recycled material containing polypropylene resin, to produce a recycled material-containing container having a reinforcing flange formed on a side wall, the method comprising: a mixing step of mixing the virgin material with the recycled material to obtain a mixed material; and a molding step of injecting the mixed material into a mold to perform injection molding. In the molding step, a mold is used in which L / T is 250 or more, where L is the maximum flow length from a resin gate and T is the thickness of a cavity. In the mixing step, an organic peroxide is added to the recycled material so as to be between 0.2% and 1.5% by mass, and titanium oxide is added to the recycled material so as to be between 2% and 6% by mass, thereby obtaining a container having a melt flow rate of 40 g / 10 min or more and a brightness of 40 g / 10 min or more. * The value must be between 45 and 65, and the flexural modulus of the container containing recycled materials must be 1100 MPa or more and the Izod impact value must be 8.0 kJ / m 2 A method for manufacturing a container containing recycled materials, characterized in that the above is achieved.

[0051] (D) A grey recycled material-containing container made of a mixture of virgin material made of polypropylene resin and modified recycled material containing polypropylene resin, the ratio of the maximum length from the resin gate mark to the thickness of the side wall being 250 or more, the melt flow rate being 40 g / 10 min or more, the titanium oxide content being 0.2% by mass or more and 5.0% by mass or less, and the specific gravity being 0.91 g / cm 3 More than 1.02g / cm 3 is less than or equal to L *The value is 36 or more and less than 65, the flexural modulus is 1100 MPa or more, and the Izod impact value is 8.0 kJ / m 2 or more, and a container containing a recycled material, characterized in that.

Examples

[0052] <Modification of recycled materials with organic peroxides> The properties and mechanical properties of the modified recycled material (peroxide-modified recycled material) were evaluated when an organic peroxide was added to the recycled material. In addition, the properties and mechanical properties of the mixed material when the modified recycled material was mixed with the virgin material were evaluated. The MFR of the recycled material before modification was 7.7 g / 10 min, the flexural modulus was 1150 MPa, and the Izod impact value was 5.7 kJ / m 2 It was.

[0053] Perbutyl (registered trademark) P-40 (manufactured by NOF Corporation) was used as the organic peroxide. The recycled material was modified by adding an organic peroxide so as to be 0.1, 0.3, 0.5, and 0.7% by mass, respectively. For the organic peroxide-modified recycled material after adding the organic peroxide, the MFR, flexural modulus, and Izod impact value were measured, respectively.

[0054] In addition, a mixed material was prepared by mixing the modified recycled material with a virgin material of polypropylene so as to be 30% by mass. The MFR of the virgin material was 52.7 g / 10 min. For the mixed material, the MFR, flexural modulus, and Izod impact value were measured, respectively.

[0055] <Measurement of MFR> The measurement was carried out using a melt indexer tester in accordance with JIS K7210 under the conditions of a temperature of 230 °C and a load of 2.16 kg.

[0056] The evaluation criteria for the MFR of the modified recycled material are as follows. 〇: The MFR is 40 g / 10 min or more, and the compatibility with the virgin material is good. △: MFR is 20 g / 10 min or more and less than 40 g / 10 min, and compatibility with virgin materials is generally good. ×: MFR is less than 20 g / 10 min, and compatibility with virgin materials is poor.

[0057] The MFR evaluation criteria for mixed materials are as follows: ◯: MFR is 40 g / 10 min or more, and the fluidity during injection molding is good. ×: MFR is less than 40 g / 10 min, and the fluidity during injection molding is not good.

[0058] <Measurement of bending elastic modulus> The measurements were performed using an autograph testing machine in accordance with JIS K7171 under the conditions of a test speed of 10 mm / min, a support distance of 60 mm, a support radius of 5 mm, and an indenter radius of 5 mm.

[0059] The evaluation criteria for flexural modulus for the mixed materials are as follows: ◯: The flexural modulus is 1100 MPa or more, and the flexural strength of the molded product is good. ×: The flexural modulus is less than 1100 MPa, and the flexural strength of the molded article is not good.

[0060] <Measurement of Izod impact value> The measurements were performed using an Izod impact tester in accordance with JIS K7110 with a hammer capacity of 2.75 J.

[0061] The evaluation criteria for the Izod impact value for the mixed materials are as follows: 〇: Izod impact value is 8kJ / m 2 As a result, the molded article has good fracture strength against impact. △: Izod impact value is 7kJ / m 2 More than 8kJ / m 2 The fracture strength of the molded article against impact is not good. ×: Izod impact value is 7 kJ / m 2 The fracture strength of the molded article against impact is not good.

[0062] The physical and mechanical properties are shown in Table 1.

[0063] [Table 1] From the results in Table 1, when 0.2% by mass or more of organic peroxide was added to the recycled material, the MFR of the modified recycled material was 20g / 10min or more, and the compatibility with the virgin material was generally good. Also, when 0.3% by mass or more of organic peroxide was added to the recycled material, the MFR of the mixed material in which the modified recycled material was mixed with the virgin material was 40g / 10min or more, and the fluidity was good.

[0064] On the other hand, if the amount of organic peroxide added to the recycled material is 1.5 mass% or less, the flexural modulus of the mixed material is 1100 MPa or more, and the Izod impact value is 7 kJ / m 2 In particular, when the amount of organic peroxide added was 0.6 mass % or less, the flexural modulus was 1100 MPa or more, and the Izod impact value was 8 kJ / m or more. 2 As a result, the mechanical strength of the molded product was further improved.

[0065] <Improvement of recycled materials with titanium dioxide> The properties and mechanical properties of the modified recycled material (modified titanium oxide recycled material) were evaluated when titanium oxide was added to the recycled material. In addition, the brightness of the mixed material was evaluated when the modified recycled material was mixed with virgin material. The recycled material before modification was L * Values ​​of 30 and 35 were used.

[0066] The recycled material was modified by adding titanium oxide to it at 2, 4, 6, and 8 mass%. The modified recycled material after adding titanium oxide was L * The value was measured and the brightness was judged. * Value, b * The values ​​were measured to judge the hue and saturation.

[0067] The modified recycled material was mixed with virgin polypropylene material at 10, 30, and 50 mass% to prepare mixed materials. * The value is 57.47, a * The value is -1.59, b * The value was 1.17. For the mixed materials, * Value, a * Value, b * The value and specific gravity were measured.

[0068] In addition, a * The value is preferably within -2 so as not to make the green color stronger, and is preferably 0 or less so as to make the red color less noticeable. * The value is preferably within −5 to prevent the blue from becoming too strong, and is preferably 0 or less to make the yellow difficult to perceive.

[0069] <L * Value Measurement> Based on JIS Z8722, a spectrophotometer is used to measure the L * The values ​​were measured.

[0070] L of mixed materials * The evaluation criteria (brightness judgment) for the values ​​are as follows: ◎;L * A value between 45 and 60 results in a grey colour similar to that of virgin material. 〇;L * The value is between 36 and 45, resulting in a slightly darker grey colour than virgin material, or * The value is between 60 and 65, resulting in a slightly lighter grey colour than virgin material. △;L * It has a value between 65 and 70, resulting in a slightly lighter grey colour than virgin material. ×;L * If the value is less than 36, the overall color will be dark, or * A value of 70 or above results in an overall whitish appearance.

[0071] <Measurement of specific gravity> Measurements were performed using an electronic specific gravity meter in accordance with JIS K7112. The properties of the titanium oxide modified recycled material are shown in Table 2.

[0072] [Table 2] When titanium dioxide is added to the recycled material in an amount of 2% by mass to 10% by mass, the L * The L value was 35 or more and less than 70. In addition, the L value of the mixed material in which the modified recycled material was mixed with the virgin material was * The value was between 35 and 70, resulting in a gray color of about the same brightness as containers made from virgin materials.

[0073] From the results in Table 2, L * When titanium dioxide is added to a recycled material with a L value of 35 so that the amount is between 2% and 4% by mass, the L value of the modified recycled material is * The L value was 50 or more and less than 65. In addition, the L value of the mixed material, which is a mixture of modified recycled material and virgin material, * The value was between 50 and 65, which was neither too black nor too white, resulting in a gray color of about the same brightness as containers molded from virgin materials.

[0074] L * When titanium dioxide is added to a recycled material with a L value of 30 so that the amount is between 2% and 6% by mass, the L value of the modified recycled material is * The L value was 45 or more and less than 60. In addition, the L value of the mixed material, which is a mixture of modified recycled material and virgin material, * The value was between 45 and 60, which was neither too black nor too white, resulting in a gray color of about the same brightness as containers molded from virgin materials.

[0075] From the results in Table 2, L * When titanium dioxide is added to a recycled material with a L value of 31 to 35 in an amount of 2 to 6 mass%, the L value of the modified recycled material is * The L value was 36 or more and less than 65. In addition, the L value of the mixed material, which is a mixture of modified recycled material and virgin material, *The value was between 36 and 65, which was neither too black nor too white, resulting in a gray color of about the same brightness as containers made from virgin materials. [Explanation of symbols]

[0076] 1. Container 11...Bottom wall 12…Side wall 16...Vertical flange 17...Horizontal flange

Claims

1. A method for manufacturing a container containing recycled materials by injection molding a gray mixed material obtained by mixing a virgin material made of polypropylene resin with a recycled material containing polypropylene resin, A mixing step of mixing the virgin material with the recycled material, In the mixing step, an organic peroxide is added, and the recycled material modified by adding titanium oxide in an amount of 2% by mass or more and 10% by mass or less is mixed, and the melt flow rate is 40 g / 10 min or more, the Izod impact value is 8.0 kJ / m 2 A method for producing a container containing recycled materials, comprising preparing the above-mentioned mixed material.

2. The method for manufacturing a container containing recycled materials according to claim 1, characterized in that in the mixing step, the recycled material is modified by adding an organic peroxide in an amount of 0.2% by mass or more and 1.5% by mass or less.

3. In the mixing step, the recycled material modified by adding titanium oxide in an amount of 2% by mass to 10% by mass is mixed, so that the specific gravity of the mixed material is 0.91 g / cm 3 1.02g / cm or more 3 3. A method for producing a container containing recycled materials according to claim 2, characterized in that:

4. The recycled material has a brightness of L * The value is 31 or more and 35 or less, The method for manufacturing a container containing recycled materials according to claim 1, characterized in that in the mixing step, the recycled material is modified by adding titanium oxide in an amount of 2% by mass or more and 6% by mass or less.

5. A grey recycled material-containing container made of a mixture of virgin material made of polypropylene resin and modified recycled material containing polypropylene resin, containing 0.2% by mass or more and 5.0% by mass or less of titanium oxide and having a specific gravity of 0.91 g / cm 3 1.02g / cm or more 3 is less than or equal to L * The value is 35 or more and less than 65, and the color is gray. The flexural modulus is 1100 MPa or more, and the Izod impact value is 8.0 kJ / m 2 A container containing recycled materials, characterized by the above.

6. 6. The recycled material-containing container according to claim 5, characterized in that the melt flow rate is 40 g / 10 min or more.

Citation Information

Patent Citations

  • Highhspeed print hammer device

    JP1980057485A